Investigation of mechanical properties of polymer impregnated concrete containing polypropylene fiber by taguchi and anova methods - Tanyildizi, Harun (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2021)
The mechanical properties of polymer impregnated concrete containing polypropylene fiber were statistically and experimentally examined in this study. Taguchi L-9 (3(3)) was used in this study. The variables used for experiments were selected as the polypropylene fiber ratio (0%, 1% and 2%), cement dosage (300, 350 and 400 kg/m(3)) and curing time (7, 14 and 28 days). After the specimens were cured at the specified curing times, they were dried at 105 +/- 5 degrees C. Then, the monomer was impregnated to the specimens for 24 hours under atmospheric conditions. The samples for the polymerization of monomer was kept within the drying oven at 60 degrees C for 6 hours. The compressive strength and ultrasonic pulse velocity tests of specimens, in which polymerization was applied, was conducted. Furthermore, the dynamic modulus of elasticity of samples was calculated using the ultrasonic pulse velocity. The Taguchi analysis found that the best values for the ultrasonic pulse velocity, dynamic modulus of elasticity and compressive strength were 28 days for curing, 1% for the polypropylene fiber percentage and 400 kg/m(3) for the cement dosage. The Anova analysis found that the polypropylene fiber percentage had the biggest effect on the mechanical properties of polymer impregnated concrete containing polypropylene fiber.
Keywords: polymer impregnated concrete; polypropylene fiber; mechanical properties; taguchi; anova analysis